Nilai Keadilan Sebagai Landasan Pembuktian dalam KUHAP Nasional - Hartati, Tutut; Hasibuan, Edi Saputra (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the concept of justice as the foundation of proof in the indonesian criminal procedure code (KUHAP) with a focus on the paradigm shift from procedural justice to substantive justice. Proof is understood not merely as a technical mechanism to fulfill formal evidentiary requirements but as an ethical and constitutional process that determines the realization of justice in criminal adjudication. Using a normative legal research approach combined with statutory, conceptual, and philosophical analyses, this study finds that the new kuhap, enacted under law no. 20 of 2025, affirms the principles of substantive justice through the recognition of electronic evidence, an open system of evidence, and the exclusionary rule for unlawfully obtained evidence. However, the implementation of substantive justice still faces cultural and structural challenges within judicial practice. Therefore, the internalization of substantive justice is essential to ensure that the system of proof not only guarantees legal certainty but also embodies justice that is humane and civilized.